PELAKSANAAN RESTORATIVE JUSTICE SEBAGAI UPAYA PEMENUHAN HAK RESTITUSI BAGI KORBAN TINDAK PIDANA PENGANIAYAAN DI PASAMAN BARAT - Utari Inaldha; Erdiansyah Erdiansyah; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Victims of criminal acts often bear their own medical expenses as a result of theirnatural criminal acts. Even though the wound or illness received by the victim was not due tohis fault but from the perpetrator of the crime. Victims seem to be sidelined to obtain justice.Especially after the issuance of Presidential Regulation No. 82 of 2018 concerning HealthInsurance Article 52 paragraph (1) letter (r). Victims of the crime of persecution whopreviously had a Social Security Administering Body card, hereinafter referred to as BPJS,can use it to ease their burden, are again sidelined and have to try to recover their conditionon their own. So the first research objective is to find out the implementation of restorativejustice as an effort to fulfill the right of restitution for victims of criminal acts of persecutionin West Pasaman. Second, knowing the efforts and obstacles in implementing restorativejustice as an effort to fulfill the right of restitution for victims of criminal acts of persecutionin West Pasaman.This research is classified into the type of sociological legal research which isengaged in the field of legal reality, on the basic aspects of law. Sources of data are primarydata and secondary data consisting of primary legal materials, secondary legal materialsand tertiary legal materials. Data collection techniques in this study were observation,interviews, and literature study.The results that can be obtained from this research are the implementation ofrestorative justice as an effort to fulfill the right of restitution for victims of abuse in WestPasaman, which can be implemented in two institutions, namely the West Pasaman ResortPolice and the West Pasaman District Attorney. The implementation of restorative justice atthe police level is carried out for those who carry out the functions of criminal investigation,investigation and investigation in the police. Whereas in the prosecutor's office it is carriedout in the prosecution, namely when the responsibility for the suspect and evidence is handedover or commonly referred to as stage two. Every restorative justice settlement can fulfill thevictim's right of restitution because it is necessary to prove that the victim's rights have beenfulfilled, then a peace agreement can be signed. Constraints and efforts in the implementationof restorative justice as the fulfillment of the right of restitution for victims of persecution inWest Pasaman, there are several obstacles encountered related to obtaining a peaceagreement between parties caused by external factors in the form of compensation paymentsand the ability of the perpetrators. Efforts made include providing mediation facilities,bringing together parties by bringing in ninik mamak as an effort to reach a peaceagreement, and providing suggestions for peace.Keywords: Restorative Justice- Mediation-Right to restitution